Computational Fluid Dynamics Analysis of the Effect of Stern Shape Modifications on Ship Resistance - Julyus Acang Suwignyo Putro; I Putu Sindhu Asmara; Priyambodo Nur Ardi Nugroho (Universitas Negeri Jakarta, 2026)
The change of the propulsion system usually involves structural modifications of the stern, which have a large impact on the hydrodynamic behaviour of the ship, e.g. the total resistance and the flow field. Calculations of the drag force and flow velocity are performed in order to investigate the effect of the stern modifications on the vessel resistance. The study was carried out by means of Computational Fluid Dynamics (CFD) simulations in the ANSYS Workbench environment. The research compared four different skeg size variants used after modification of the original hull of the ship. The simulation results show that the flow velocity of the original hull was 3.220 m/s and the drag force was 118.70 kN. Among the tested variations, variation 4 emerged as the most efficient design, yielding a reduced drag force of 81.59 kN and an increased flow velocity of 3.461 m/s. Ultimately, the proposed stern modification successfully lowered the total ship resistance from 118.70 kN to 82.93 kN, achieving a significant 30% reduction in resistance.